THE EFFECT OF POLYCARBONATE RAW MATERIAL PLANNING AND INVENTORY CONTROL ON OPERATIONAL PERFORMANCE AT PT XYZ (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to analyze the effect of Polycarbonate Raw Material planning and Inventory Control on Operational Performance at PT XYZ, an eyeglass lens manufacturing company located in Bekasi Regency. The research was motivated by the increasing gap between planned and actual polycarbonate raw material usage and repeated overstock during 2023 to 2025. This study used a quantitative approach with a survey method. Primary data were collected through questionnaires distributed to employees involved in planning, procurement, inventory, and operational activities, while secondary data were obtained from company documents. The population consisted of 78 employees, and 66 respondents were selected using purposive sampling based on the Slovin formula with a 5% error tolerance. The data were analyzed using SPSS version 26 through validity test, reliability test, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that Planning has a positive and significant influence on Operational Performance, with a t-value of 4.767, which is higher than the t-table value of 1.99834, and a significance value of 0.000. Polycarbonate Raw Material Inventory Control also has a positive and significant influence, with a t-value of 4.471 and a significance value of 0.000. Simultaneously, both variables significantly influence Operational Performance, with an F-value of 34.949 and an Adjusted R Square of 0.511. These findings indicate that accurate planning and effective inventory control are important in improving operational performance at PT XYZ.